ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA DESA - Ratnasari, Brenda; Rahmawati, Mia Ika (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This research aimed to as follows analyze the accountability of Village Fund Management at Desa Nglawak, Kecamatan Kertosono, Kabupaten Nganjuk and analyze the transparency of Village Fund Management at Desa Nglawak, Kecamatan Kertosono, Kabupaten Nganjuk with analysis steps started by planning, implementing, managing, reporting, and accountability. Moreover, the research was descriptivequantitative. The instruments in the data collection technique were observation, interviews, and documentation. The interviews were conducted with key informants, such as the Head of the Village, the secretary, the treasurer, the Head of the Wealth section, and the Head of the Planning section. The result concluded as follows the Government of Desa Nglawak had implemented the Accountability principle on the Village Fund Management which was suitable with Guidelines for the Implementation of Guidance & Consultation on Village Financial Management 2015; the Government of Desa Nglawak had implemented the Transparency principle on the Village Fund Management which was suitable with Guidelines for the Implementation of Guidance & Consultation on Village Financial Management 2015. In short, the analysis result which was based on planning, implementation, management, reporting, and accountability was suitable and well-implemented due to the Guidelines for the Implementation of Guidance & Consultation on Village Financial Management 2015.